Experiences of suicide ideation and attempts among Filipino students: Prevalence, reasons, and help-seeking behavior - Quintos, Mark Anthony (Social Sciences and Development Review, 2023)
This study sought to determine the prevalence of suicide ideation and attempts among Filipino undergraduate students before and during the pandemic. It also sought to determine the reasons as well as the help seeking behavior of the aforesaid students and find out if there are significant relationships between their socio-economic characteristics and their suicide-related behaviors. Data were obtained through a survey questionnaire (n=308) and were analyzed through descriptive statistics and Spearman Rho correlational tests. Findings showed that majority of the respondents have thought or made plans about suicide at least once. Meanwhile, 2 out of every 10 respondents coming from a predominantly richer university has attempted suicide while 4 out of every 10 from a predominantly poorer university did the same. Most of the suicide ideators thought of suicide before and during the pandemic while suicide attempts were more common before the pandemic. Most of those who experienced suicide ideation and/or attempts did not seek any form of help during the ordeal and, for those who did, the help was sought from friends instead of mental health professionals and suicide hotlines. The study also found that family problems were the most common reason for suicide before the pandemic and academic problems were the most common during the pandemic, albeit there was an observed rise in suicide ideations and/or attempts due to financial problems as well. Finally, correlational tests found that males, the religious, and the rich tend to engage in less suicide-related behaviors while the opposite was observed among LGBT students